Role of chemical peels in postinflammatory hyperpigmentation: a comprehensive review - Surabhi Dayal; Priyadarshini Sahu; Bhavya Sangal; Shruti Sharma (Wolters Kluwer Medknow Publications, 2019)
Postinflammatory hyperpigmentation (PIH) is an acquired hypermelanosis arising after inflammation or injury to the skin and can develop in all skin types especially in Fitzpatrick skin phototypes III to VI. In higher skin phototypes, chances of PIH following procedures using laser and other light sources are high. Therefore, it is becoming increasingly important to manage this unforeseen condition. Wide variety of treatment options are available for PIH, but there is limited literature regarding efficacy and safety of chemical peels in PIH. Hence, a thorough systematic review was performed by searching Pubmed, Scopus, Medline, and Cochrane databases in English language involving studies on PIH. Thus, this article is an attempt to bring together all the possible ways of using chemical peels (alone, in combination with other peels or topical agents) for the management of PIH.